2003
DOI: 10.1002/jae.697
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in first‐price auctions with affiliated private values

Abstract: SUMMARYCollusion and heterogeneity across firms may introduce asymmetry in bidding games. A major difficulty in asymmetric auctions is that the Bayesian Nash equilibrium strategies are solutions of an intractable system of differential equations. We propose a simple method for estimating asymmetric first-price auctions with affiliated private values. Considering two types of bidders, we show that these differential equations can be rewritten using the observed bid distribution. We establish the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
106
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 41 publications
1
106
2
5
Order By: Relevance
“…In such settings, the researcher may control for unobserved characteristics by conditioning on the bidder makeup of an auction (i.e., the number of total bidders, the number of bidders of different types, etc.). Campo et al (2003) suggested a means for testing for unobserved heterogeneity along these lines. Remember that the authors considered OCS wildcat auctions with two types of bidders: solo and joint bidders.…”
Section: Unobserved Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…In such settings, the researcher may control for unobserved characteristics by conditioning on the bidder makeup of an auction (i.e., the number of total bidders, the number of bidders of different types, etc.). Campo et al (2003) suggested a means for testing for unobserved heterogeneity along these lines. Remember that the authors considered OCS wildcat auctions with two types of bidders: solo and joint bidders.…”
Section: Unobserved Heterogeneitymentioning
confidence: 99%
“…For this reason, tests of common versus private values that were developed after Laffont and Vuong (1996) were mostly based on observations of varying numbers of bidders across different auctions. Campo et al (2003) discovered a method for testing the appropriateness of the PCV information structure when bidders are asymmetric. Since in a PCV model it is only bidders' signals of value which differ, it turns out that bidding strategies do not actually differ across bidder types.…”
Section: Testing Common Versus Private Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, conditioning on (Z,N ) indirectly fixes the realization of V 0 , making it possible to estimate the right-hand side of (3.10) (Campo, Perrigne, and Vuong (2003), Haile, Hong, and Shum (2003)). This can be thought of as using a set of observable outcomes as "control functions" for the unobservable.…”
Section: Unobserved Heterogeneitymentioning
confidence: 99%
“…Although it is of direct relevance to procurement auctions where engineering and construction firms may submit a joint proposal (Iimi, 2004;Albano et al, 2009), it is interesting to note that much of what we know empirically about the effect of joint bidding comes from a series of studies of auctions for land leases and off-shore drilling rights for oil and gas by the U.S. federal government (Mead, 1968;DeBrock and Smith, 1983;Hendricks, Porter and Tan, 2008;Hendricks and Porter, 1992;Campo, Perrigne and Vuong, 2003).…”
mentioning
confidence: 99%